Perngaruh Kepercayaan dan Pengalaman Pembelian terhadap Minat Beli Ulang secara Online di Shopee: Survei pada Mahasiswa Universitas Singaperbangsa Karawang - Nurul Aulia; Sinta Apriyani; Abdul Yusuf (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to determine the extent of the influence of trust, purchasing experience on online repurchase interest in shopee case studies of Singaperbangsa University Karawang students in 2024. With a sample size of 100 respondents through a quantitative approach. This study uses multiple linear regression analysis with the help of SPSS software. The results showed that the influence of trust has a significant influence on online repurchase interest in students of Singaperbangsa University Karawang in 2024. Purchasing experience has a significant influence on online repurchase interest in students of Singaperbangsa University Karawang in 2024.